MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI PENERAPAN METODE EJA PADA PESERTA DIDIK KELAS 2 SDN 02 MANANGGU KABUPATEN BOALEMO - Yane Hardiyanti Mahmud; Sumarni Ibura (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2024)
The purpose of this research was to improve the literacy skills of grade 2 students at SDN 02 Mananggu, Boalemo Regency. The method used is classroom action research with research subjects, namely class 2 students, amounting to 24 students. This research was conducted in the form of a cycle and each cycle consisted of 4 stages, namely the planning stage, the action implementation stage, the observation and evaluation / reflection stages. This results of students' letter recognition skills are still in the low category. This is indicated by the low level of student learning activities in the ability to recognize letters at the time of initial observation on good aspects, with a percentage level of 25% of the 24 students. Therefore, researchers took action using the spelling method in the ability to recognize letters. From the results of research conducted on the ability to recognize students' letters, there was an increase in the good aspects of 33.3% in the first cycle of the first meeting, 41.6% in the first cycle of the second meeting and 62.5% in the first cycle of the third meeting. Whereas in the second cycle of the first meeting, the increase in the ability to recognize letters reached 70.8% and in the second cycle the second meeting had an increase of up to 87.5%.